2020
DOI: 10.1177/0095798420979794
|View full text |Cite
|
Sign up to set email alerts
|

Examining Psychosociocultural Influences as Predictors of Black College Students’ Academic Self-Concept and Achievement

Abstract: Using the psychosociocultural framework, this study concurrently examined the influence of psychological (academic self-concept and academic engagement attitudes), social (caring student-faculty relationships), and cultural variables (racial centrality and perceived university environment) on the academic achievement of Black college students. Participants were 247 Black collegians recruited from a large, Southwestern predominately White institution. Results of structural equation modeling largely supported hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Research on the direct association between racial centrality and academic achievement among Black youth has also been mixed. In particular, some research has found a direct, positive association between centrality and achievement (Beasley & McClain, 2021), whereas other studies have found either no association or a direct, negative one (e.g., Okeke et al, 2009; Thomas et al, 2009). In a recent meta-analysis, Miller-Coto and Byrnes (2016) found that centrality was not a significant predictor of achievement.…”
Section: Racial Centralitymentioning
confidence: 99%
“…Research on the direct association between racial centrality and academic achievement among Black youth has also been mixed. In particular, some research has found a direct, positive association between centrality and achievement (Beasley & McClain, 2021), whereas other studies have found either no association or a direct, negative one (e.g., Okeke et al, 2009; Thomas et al, 2009). In a recent meta-analysis, Miller-Coto and Byrnes (2016) found that centrality was not a significant predictor of achievement.…”
Section: Racial Centralitymentioning
confidence: 99%
“…Since then, other scholars have found the PSC framework useful for understanding how Latine (J. Castellanos & Gloria, 2007; Chun et al, 2016; Dueñas & Gloria, 2017, 2020; Gloria et al, 2017), African American (Beasley, 2021; Beasley & McClain, 2021), Asian American (Gloria & Ho, 2003), and SOCs at large (Bauman et al, 2019; Her & Gloria, 2016) navigate incongruencies between their home and institutional cultures and persist in college.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several studies have also demonstrated that the university environment (e.g., feeling valued or comfortable on campus) plays a crucial role in the psychological well-being of Latina/o students on campus (Aguinaga & Gloria, 2015; Delgado-Guerrero & Gloria, 2013; Herrera et al, 2018). The PSC framework has also been used with several other groups of students of color (e.g., Native American, Black, Chinese-American, Hmong), aside from Hispanic students, and has been associated with similar positive results (see Beasley and McClain [2021] for a thorough literature review). However, no PSC study to date has investigated graduation outcomes and only one study has examined Latina/o FGCS (i.e., Dueñas and Gloria, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%